Dietary patterns and the neoplastic‐prone tissue landscape of old age. Issue 1 (24th October 2020) - Marongiu, Fabio; Laconi, Ezio
Abstract: There is now sufficient evidence to indicate that aging is associated with the emergence of a clonogenic and neoplastic‐prone tissue landscape, which fuels early stages of cancer development and helps explaining the rise in cancer incidence and mortality in older individuals. Dietary interventions are among the most effective approaches to delay aging and age‐related diseases, including cancer. Reduced caloric intake has been, historically, the most intensely investigated strategy. Recent findings point to a critical role of a long fasting interval in mediating some of the beneficial effects of caloric restriction. Time‐restricted feeding, intermittent fasting, and fasting mimicking diets are being proposed for their potential to prolong healthy life span and to delay late‐onset diseases such as neoplasia. Evidence will be discussed suggesting that the effects of these dietary regimens are mediated, at least in part, through retardation of age‐related functional changes at cell and tissue level, including a delay in the emergence of the neoplastic‐prone tissue microenvironment. Abstract : Dietary interventions such as caloric restriction, time‐restricted feeding, and/or intermittent fasting exert their protective effects on the risk of neoplastic disease via modulation of age‐associated changes in the tissue landscape. The latter include, but are not limited to, alterations in metabolism, autophagy, proteostasis, circadian rhythms, DNA methylation, inflammatory markers, and microbiota composition, all of which can contribute to the emergence of conditions favoring survival and selection of altered cell clones, including those with neoplastic potential.